Analisis Pemasaran Terhadap Keputusan Pembelian Ayam Broiler (Pada PT. Ciomas Adisatwa di Payakumbuh) - nasfi, nasfi; Eka, Febrianti (El-kahfi | Jurnal Ekonomi Islam, 2022)
This study aims to examine and analyze the effect of the marketing mix, namely product, price, promotion and distribution on broiler sales decisions at Company Ciomas Adisatwa Payakumbuh. The population in this study includes all consumers of broiler chickens Company. There are 35 active Ciomas Adisatwa people. Data was obtained by distributing questionnaires directly to respondents. The data analysis method used is Instrument Test, namely Validity Test and Reliability Test, Regression Model Determination Test and Variable Descriptive Analysis (TCR). The analytical tool used is Binary Logistics Regression Analysis. The results obtained are (1) the product has a positive and insignificant effect on the purchasing decision of Payakumbuh broiler chickens. (2) Price has a positive and insignificant effect on purchasing decisions of Payakumbuh broiler chickens. (3) Promotion has a positive and insignificant effect on purchasing decisions of Payakumbuh broilers. (4) Distribution channels have no positive and significant effect on purchasing decisions of Payakumbuh broilers.